Balancing Power in Decentralized Governance: Quadratic Voting and Information Aggregation - Benhaim, Alon; Falk, Brett Hemenway; Tsoukalas, Gerry (Management Science, 2026)
In decentralized governance, quadratic voting (QV)—where the cost of acquiring voting power is convex—optimally aggregates voter preferences, outperforming simpler linear voting (LV) mechanisms when voters have complete information. But what if they do not? We show that uncertainty not only breaks QV optimality but can also cause it to underperform LV. Intuitively, this is because cost convexity can disincentivize better-informed voters from adequately conveying their private information. The optimal mechanism varies with the distribution of stakes and information among voters, implying that QV’s known advantages in preference aggregation do not readily extend to common-value information aggregation settings. This paper was accepted by Will Cong for the Special Issue on the Digital Finance. Supplemental Material: The online appendices are available at https://doi.org/10.1287/mnsc.2024.08469 .